UNDERSTANDING DOCTORS' ETHICAL CHALLENGES AS ROLE VIRTUE CONFLICTS - Mcdougall, Rosalind (Bioethics, 2013)
This paper argues that doctors' ethical challenges can be usefully conceptualised as role virtue conflicts. The hospital environment requires doctors to be simultaneously good doctors, good team members, good learners and good employees. I articulate a possible set of role virtues for each of these four roles, as a basis for a virtue ethics approach to analysing doctors' ethical challenges. Using one junior doctor's story, I argue that understanding doctors' ethical challenges as role virtue conflicts enables recognition of important moral considerations that are overlooked by other approaches to ethical analysis.